2015
DOI: 10.1088/0067-0049/216/1/13
|View full text |Cite
|
Sign up to set email alerts
|

Leaving the Dark Ages With Amiga

Abstract: We present an Analytic Model of Intergalactic-medium and GAlaxy evolution since the dark ages. AMIGA is in the spirit of the popular semi-analytic models of galaxy formation, although it does not use halo merger trees but interpolates halo properties in grids that are progressively built. This strategy is less memory-demanding and allows one to start the modeling at redshifts high enough and halo masses low enough to have trivial boundary conditions. The number of free parameters is minimized by making the cau… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 121 publications
0
9
0
Order By: Relevance
“…Finally, given that there are few observables that are sensitive to the thermal state of baryons at the earliest redshifts, the 1D flux power spectrum at z 5 offers a unique opportunity to explore not only H i reionization, but also constrain other physical scenarios that alter the thermal history of the IGM, for example, models that alter the thermal state of the IGM via X-ray preheating coming from starburst galaxies, supernova remnants or miniquasars (Oh 2001;Glover & Brand 2003;Madau et al 2004;Furlanetto 2006;Madau & Fragos 2017), dark matter annihilation or decay (Liu et al 2016), cosmic rays (Samui et al 2005), blazar heating (Chang et al 2012;Puchwein et al 2012), broadband intergalactic dust absorption (Inoue & Kamaya 2008) or high-z exotic reionization scenarios driven by Population III stars (e.g. Manrique et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, given that there are few observables that are sensitive to the thermal state of baryons at the earliest redshifts, the 1D flux power spectrum at z 5 offers a unique opportunity to explore not only H i reionization, but also constrain other physical scenarios that alter the thermal history of the IGM, for example, models that alter the thermal state of the IGM via X-ray preheating coming from starburst galaxies, supernova remnants or miniquasars (Oh 2001;Glover & Brand 2003;Madau et al 2004;Furlanetto 2006;Madau & Fragos 2017), dark matter annihilation or decay (Liu et al 2016), cosmic rays (Samui et al 2005), blazar heating (Chang et al 2012;Puchwein et al 2012), broadband intergalactic dust absorption (Inoue & Kamaya 2008) or high-z exotic reionization scenarios driven by Population III stars (e.g. Manrique et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…To check this idea, we run the self-consistent Analytic Model of Intergalactic-medium and GAlaxy (AMIGA; Manrique et al 2015) which successfully recovers the observed properties of the high-z universe (Salvador-Solé et al 2017). The idea is not to do an in-depth study of the results of the run, as this will be part of a dedicated upcoming work, but rather to simply test whether there is any theoretical support for such a claim.…”
Section: The Nature Of High Star Formation Rates In Quasar Hostsmentioning
confidence: 99%
“…To check the performance of this improved treatment of IGM we coupled it to the galaxy model by Manrique et al (2015) for realistic values of the parameters leading to double reionization (Salvador-Solé & Manrique 2014). The main results were as follows:…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the present paper is to improve the analytical treatment of IGM evolution by deriving new more accurate master equations for its ionization state and temperature, and by estimating the halo ionization-bias necessary to properly compute the source functions in these equations. Such an improved treatment of IGM can be incorporated into any given (semi)numerical or (semi)analytic model of galaxy formation such as the one developed by Manrique et al (2015). The IGM properties shown throughout the paper to illustrate the effects of the new treatment have been obtained from that model.…”
Section: Introductionmentioning
confidence: 99%